Genome-resolved metagenomic analysis of Great Amazon Reef System sponge-associated Latescibacterota bacteria and their potential contributions to the host sponge and reef - Oliveira, Rafael S.; Pinto, Otávio H. B.; Quirino, Betania F.; de Freitas, Mayanne A. M.; Thompson, Fabiano Lopes; Thompson, Cristiane; Kruger, Ricardo H. (Frontiers in Microbiomes, 2023)
The Great Amazon Reef System (GARS) is an extensive biogenic reef influenced by a plume layer of sediments. This creates an extreme environment where light is reduced, thus affecting physicochemical properties as well as living organisms such as sponges and their microbiomes. The sponge's microbiome has numerous ecological roles, like participation in biogeochemical cycles and host nutrition, helping the sponge thrive and contributing to the ecosystem. Also, sponges and spongeassociated microorganisms are rich sources of bioactive compounds, and their products are applied in different areas, including textile, pharmaceutical, and food industries. In this context, metagenomeassembled genomes (MAG), obtained from GARS sponges microbiota, were analyzed to predict their ecological function and were prospected for biotechnological features. Thus, in this work, tissues of GARS sponges were collected, their metagenomes were sequenced and assembled, and 1,054 MAGs were recovered. Ten of those MAGs were selected based on their taxonomic classification in the candidate phylum Latescibacterota and this group's abundance in GARS sponges. The workflow consisted of MAG's quality definition, taxonomic classification, metabolic reconstruction, and search for bioactive compounds. Metabolic reconstruction from medium to high-quality MAGs revealed genes related to degradation and synthesis pathways, indicating functions that may be performed by GARS sponge-associated Latescibacterota. Heterotrophy, a recurring attribute in Latescibacterota that Deleted: 10 34 Deleted: of the candidate phylum Latescibacterota might be crucial for GARS sponge holobiont nutrition, was verified by the presence of genes related to respiration and fermentation. Also, the analyzed bacteria may contribute to the host's survival in multiple ways, including host protection via defense systems; aid in nutrient consumption by breaking complex substrates and producing essential nutrients like vitamins and certain amino acids; and detoxification of mercury, arsenic, ammonia, and hydrogen sulfide. Additionally, genes linked to persistent organic pollutant degradation, including glyphosate, and biogeochemical cycles reactions, such as ammonification, sulfate reduction, thiosulfate disproportionation, phosphorus remineralization, and complex organic matter degradation, were identified, suggesting the participation of these Latescibacterota in bioremediation and nutrient cycling. Finally, the investigated MAGs contain genes for numerous bioactive compounds, including industrial enzymes, secondary metabolites, and biologically active peptides, which may have biotechnological value.